2020
DOI: 10.2147/cia.s265839
|View full text |Cite
|
Sign up to set email alerts
|

<p>Influence of Lifestyles on Mild Cognitive Impairment: A Decision Tree Model Study</p>

Abstract: Objective To explore the effects of different lifestyle choices on mild cognitive impairment (MCI) and to establish a decision tree model to analyse their predictive significance on the incidence of MCI. Methods Study participants were recruited from geriatric and physical examination centres from October 2015 to October 2019: 330 MCI patients and 295 normal cognitive (NC) patients. Cognitive function was evaluated by the Mini-Mental State Examination Scale (MMSE) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…In Su et al ( 20 ) study, they found that hobbies, such as reading, surfing the internet, were protective factors for MCI. In Wang et al's ( 21 ) study, they found that hobbies could help prevent MCI. In Shimada et al's ( 22 ) study, they found that participating in hobbies or sports activities would help reverse MCI.…”
Section: Discussionmentioning
confidence: 99%
“…In Su et al ( 20 ) study, they found that hobbies, such as reading, surfing the internet, were protective factors for MCI. In Wang et al's ( 21 ) study, they found that hobbies could help prevent MCI. In Shimada et al's ( 22 ) study, they found that participating in hobbies or sports activities would help reverse MCI.…”
Section: Discussionmentioning
confidence: 99%
“…BADLs are commonly measured using the barthel index (BI) 42 , and various studies involving this index have been published in older adults 43 , patients with stroke 11 , and those with cognitive impairment 44 . Validity and reliability of Chinese version of BI have been substantiated in both Taiwanese and Chinese older adults 45 , 46 .…”
Section: Methodsmentioning
confidence: 99%
“…However, it is worth specifying that the aforementioned meta-analysis mostly considered patients with a diagnosed depression, while we opted for a brief screening tool, i.e., the Geriatric Depression Scale (GDS), for excluding major depression. The same can be noted for other well-known reliable protective/risk factors against/favoring developing MCI and dementia, such as, physical activity, smoking, alcohol consumption, and BMI, e.g., [ 69 , 70 , 71 , 72 ]. Regarding physical activity, we can speculate that the use of a single item, as in this study, may be insufficiently sensitive in capturing the variability within habits among our study participants.…”
Section: Discussionmentioning
confidence: 54%